Interventions to improve mental help-seeking behaviours in individuals with depressive symptoms: a systematic review and meta-analysis - Shiqian Ni; Shengnan Cong; Jingyi Feng; Xiaoqing Sun; Hongyan Xie; Jingjing Han; Yaxuan Wu; Mengyao Wang; Aixia Zhang (BMC Psychiatry)
Abstract Background Several individuals with depressive symptoms either do not seek help or delay treatment. This study elucidates the effects of various interventions on help-seeking behaviours, key intermediate indicators of behaviour (intentions, attitudes, subjective norms, and perceived behavioural control), and stigma. Methods Six databases were searched from their inception to January 2024. Two researchers independently conducted study selection, data extraction, and quality appraisal. Data were analysed using Review Manager 5.4 software and STATA 18.0 software. Results Thirteen studies were included, encompassing seven types of interventions: positive emotion infusion, information support intervention, mental contrasting with implementation intentions, self-perspective interventions, telephone care management, health information feedback, and depression follow-up monitoring. Existing interventions did not improve help-seeking behaviour in individuals with depressive symptoms (OR = 1.67, 95% CI: 1.05, 2.94, P = .05) but improved help-seeking intentions immediately after the intervention (SMD = 0.64, 95% CI: 0.20, 1.08, P < .001). Subgroup analyses showed that mental contrasting with implementation intentions (SMD = 0.62, 95% CI: 0.37, 0.88) was more effective than positive emotion infusion (SMD = 0.20, 95% CI: 0.06, 0.34) in enhancing help-seeking intentions. Additionally, mental contrasting with implementation intentions improved help-seeking intentions 2 weeks after the intervention (MD = 4.44, 95% CI: 2.60, 6.28, P < .001). Providing information support positively affected attitudes toward help-seeking (MD = 0.36, 95% CI: 0.16, 0.57, P < .001). No study measured subjective norms and perceived behavioural control. Moreover, available research was insufficient to provide reliable results concerning help-seeking stigma. Conclusion Existing interventions improved help-seeking intentions in individuals with depressive symptoms but did not affect help-seeking behaviour, warranting further research. Additionally, researchers should explore the role of interventions on subjective norms, perceived behavioural control, and stigma. Future studies should consider long-term follow-up of improved help-seeking behaviour and compare the effects of different interventions. Registration number PROSPERO CRD42024496771.